Effect of alumina and halloysite clay in silicone rubber nanocomposite on the electrical tree characteristics - Ismail, Mohd Hafiz (2016)
The research on the effect of nanofiller in SiR on the dielectric properties is still new. Thus, it needs to be explored to expand on past work in the field for better understanding. It has been reported that research on nano-alumina and halloysite nanoclay have been carried out where the nanofillers has an ability to enhance the electrical and mechanical properties in other polymer material such as in epoxy and LDPE nanocomposites. Thus in this research, the influence of nano-alumina and halloysite nanoclay in SiR on the electrical tree characteristics tree such as tree inception voltage (TIV), electrical tree growth process, probability occurrences of electrical tree structure, types of electrical tree, electrical tree length and electrical tree growth rate are investigated. In addition, maximum of electrical field, accumulate damage and expansion coefficient are also studied and investigated. Surface morphology analysis of SiR/Alumina nanocomposites and SiR/Halloysite clay nanocomposites using Scanning Electron Microscopy (SEM) are also performed. Furthermore, the inter particle distance of nanofiller (surface to surface) in SiR/Alumina nanocomposites analyzed from SEM images are evaluated using ImageJ software and inter particles distance equation is also discussed. The results have revealed that 2 vol% nano-alumina has an ability to improve the electrical tree characteristics such as tree inception voltage (TIV), electrical tree length, electrical tree growth rate compared to unfilled SiR. However the increase of nano-alumina up to 3 vol% drops the TIV and contributes to rapid electrical tree growth rate and insulation breakdown. On the other hand, the presence of halloysite nanoclay up to 3 vol% in SiR has improved the TIV, electrical tree length,electrical tree growth rate compared to the unfilled SiR. It is shown that, the addition of nano-alumina up to 2 vol% and up to 3 vol% for halloysite nanoclay in SiR tends the tree structure appeared in bush type tree. Furthermore, it has also increased the maximum electrical field, reduced the percentage of accumulate damage and the expansion coefficient is varied almost to unity. In addition, the result from SEM image analysis depicted that nano-alumina is homogenously dispersed up to 2 vol% however further increase of 3 vol% nano-alumina in SiR yielded to the filler agglomeration. The inter particle distance of nano-alumina (surface to surface) in SiR/Alumina nanocomposites at 1 vol% and 2 vol% are considered similar evaluated by using ImageJ software and inter particles distance equation. Meanwhile, the halloysite nanoclay in SiR is homogenously dispersed up to 3 vol%.